Prognostic Utility of Optical Coherence Tomography for Visual Outcome After Extended Endoscopic Endonasal Surgery for Adult Craniopharyngiomas - Qiao, Ning; Li, Chuzhong; Xu, Jing; Ma, Guofo; Kang, Jie; Jin, Lu; Cao, Lei; Liu, Chunhui; Zhang, Yazhuo; Gui, Songbai (Frontiers in Oncology, 2022)
Introduction: Owing to the close vicinity of the optic chiasma, visual dysfunction is known as one of the most common surgical indications and postoperative complications in adult patients with craniopharyngiomas, probably leading to poor quality of life. Historically, very few consistent predictive factors associated with the visual outcome are identified, which may be not helpful for patient counseling and preoperative decision making. Recently, optical coherence tomography (OCT) serving as a novel high-resolution imaging technique can assess the retinal morphology by measuring the circumpapillary retinal nerve fiber layer (cpRNFL) and macular ganglion cell complex thickness. However, few studies have examined the prognostic utility of OCT parameters for visual outcome after surgery for craniopharyngiomas. This study aims to use the largest series to evaluate the association between OCT parameters and visual outcome after extended endoscopic endonasal surgery (EEES) for primary craniopharyngiomas in adults. Material and Methods: From October 2018 to October 2020, one hundred and seventy eyes in 88 adult patients with newly confirmed craniopharyngiomas were retrospectively reviewed and pertinent prognostic factors were analyzed. Results: Gross total resection was performed in 82 (93.2%) patients. The median postoperative follow-up time was 10.9 months. Multiple logistic regression analysis showed that increased temporal cpRNFL thickness was associated with higher odds of visual acuity (VA) improvement and maintenance (OR=1.070; 95%CI,1.005-1.140; p=0.035), and greater inferior cpRNFL thickness was significantly associated with visual field (VF) improvement and maintenance (OR=1.034; 95%CI, 1.001-1.068; p=0.046). Furthermore, tight adhesion between optic nerves and craniopharyngiomas was demonstrated as an independent adverse factor for either postoperative VA or VF (p=0.048, p=0.030, respectively). The ROC results further verified the robustness of the prediction model either in VA (AUC=0.843; 95%CI, 0.734-0.952; p<0.001) or VF (AUC=0.849; 95%CI, 0.741-0.958; p<0.001). Conclusion: Preoperative OCT can effectively predict visual outcome after EEES for adult craniopharyngiomas. It can also serve as a reliable alternative to evaluate preoperative visual field defects, especially for patients with lower compliance. Tight adhesion was confirmed as an independent risk factor for postoperative visual outcome. The OCT-based multivariable prediction models developed in the present study may contribute to patient counseling on visual prognosis.